Localizing Epileptic Foci Before Surgery in Patients With MRI-Negative Refractory Epilepsy Using Statistical Parameter Mapping and Three-Dimensional Stereotactic Surface Projection Based on 18F-FDG PET - Zhou, Hailing; Zhang, Wei; Tan, Zhiqiang; Zhou, Ziqing; Li, Ying; Zhang, Shaojuan; Zhang, Lingling; Gan, Jiefeng; Wu, Huanhua; Tang, Yongjin; Cheng, Yong; Ling, Xueying; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Patients with refractory epilepsy are not only free of seizures after resecting epileptic foci, but also experience significantly improved quality of life. Fluorine-18-fluorodeoxyglucose positron-emission tomography (18F-FDG PET) is a promising avenue for detecting epileptic foci in patients with magnetic resonance imaging (MRI)-negative refractory epilepsy. However, the detection of epileptic foci by visual assessment based on 18F-FDG PET is often complicated by a variety of factors in clinical practice. Easy imaging methods based on 18F-FDG PET images, such as statistical parameter mapping (SPM) and three-dimensional stereotactic surface projection (3D-SSP), can objectively detect epileptic foci. This study retrospectively analyzed the ability of visual assessment, SPM and 3D-SSP based on 18F-FDG PET to detect epileptic foci in MRI-negative refractory epilepsy patients and obtained the sensitivities of visual assessment, SPM and 3D-SSP are 57%, 71% and 61% respectively. SPM was the most sensitive of the three methods while threshold (P) < 0.005 and voxel (K) > 200 (uncorrected). The result of 3D-SSP was similar to visual assessment at a Z-value of 1.28. The combination of two or three methods increased sensitivity, but decreased consistency, in localizing epileptic foci. We conclude SPM and 3D-SSP can be used as objective methods to localize epileptic foci before surgery in patients with MRI-negative refractory epilepsy.